Impact of COPD on Outcome in Patients Undergoing Transfemoral versus Transapical TAVI - Mach, Markus; Koschutnik, Matthias; Wilbring, Manuel; Winkler, Bernhard; Reinweber, Matthias; Alexiou, Konstantin; Kappert, Utz; Adlbrecht, Christopher; Delle-Karth, Georg; Grabenwöger, Martin; Matschke, Klaus Ehrhard (The Thoracic and Cardiovascular Surgeon, 2019)
Objective The purpose of this study was to evaluate the impact of chronic obstructive pulmonary disease (COPD) on clinical outcomes in patients referred for transfemoral (TF) as well as transapical (TA) aortic valve implantation and furthermore to delineate possible advantages of the TF access.Methods One thousand eight hundred forty-two patients undergoing transcatheter aortic valve implantation (TAVI) at two study centers were included in the present analysis. The outcome was measured and classified according to Valve Academic Research Consortium-II criteria. Kaplan–Meier estimate was used to assess long-term survival.Results The present analysis suggests that COPD has limited influence on post-procedural outcome after TAVI. Comparing the TF to TA approach, no significant difference on the impact of COPD on clinical outcomes has been found, except for longer post-procedural ventilation times in COPD patients treated via TA access (p < 0.001).Conclusions COPD in patients referred for TAVI procedure was associated with poorer overall long-term survival, thus characterizing a high-risk population for futile treatment; however, the selection of access did not result in a significant difference in most Valve Academic Research Consortium-II-defined clinical outcomes in COPD patients.
Keywords: TAVI; COPD; transfemoral; transapical; clinical outcome; survival